Redefining Challenges in English Listening Comprehension through Ellipsis Repair, Boundary Overrun, and Disfluent Clause Markers - Stevani, Margaret; Wijayati, Wahyu; Tarigan, Jenheri Rejeki; Saragi, Alexander Adrian (Journal of English Language and Education, 2025)
This study redefined English listening comprehension in the Indonesian EFL context by analyzing the interpretive challenges posed by ellipsis repair, boundary overrun, and disfluent clause markers features that were often overlooked in pedagogical models. Ellipsis repair referred to a listener’s attempt to reconstruct omitted elements in spontaneous speech, often caused by speakers backtracking or self-correcting mid-utterance. Boundary overrun described a speaker’s tendency to extend or blur syntactic units across intonation or clause boundaries, which made real-time parsing difficult. Disfluent clause markers included fillers, false starts, and hesitations that interrupted clause structure and challenged linear meaning construction. Conducted at three private universities in Indonesia located on Medan (North Sumatra), Manado (North Sulawesi), and Makassar (South Sulawesi), the research involved pre-intermediate-level students who engaged with authentic spoken English data. Using a qualitative discourse-based approach, the study examined comprehension breakdowns through think-aloud protocols and clause-level analysis. Findings revealed that listener difficulties were not incidental but structurally rooted in disrupted syntax and prosody. These disruptions challenged students’ ability to construct coherent meaning in real time. The study highlighted the need for instructional models that developed interpretive resilience, not just lexical decoding. It called for a shift toward listening pedagogies attuned to spontaneous speech, structural ambiguity, and repair negotiation. The findings offered implications for EFL curriculum design, assessment development, and real-world communication training across Indonesian educational contexts.